2013
DOI: 10.3382/japr.2012-00558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a monocomponent protease on performance and protein utilization in 1- to 26-day-of-age turkey poults

Abstract: A study was conducted to evaluate effects of supplementation of a monocomponent protease on growth performance and protein utilization in Nicholas turkeys from 1 to 26 d of age fed corn-soy diets with reduced levels of CP and amino acids. Poults were placed into 40 batteries of 15 birds, and allocated to 5 treatments with 8 replicates each. A positive control diet [PC, 27.94% CP, 1.69 digestible Lys (DLys)] and a negative control diet (NC1; 24.21% CP, 1.46% DLys) were formulated. A second NC diet (NC2; 23.20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…A specific enzyme, protease, was suggested adding to the feed efficiency, aimed to improve the protein utilization of the animals and reduce the required amount of dietary protein (and the nitrogen content) (Li et al, 2015;Oxenboll, Pontoppidan, & Fru-Nji, 2011). But it would also be expected to reduce the total content of nitrogen in manure helping to reduce nutrient excretions (Fru-Nji, Kluenter, Morten, & Pontoppidan, 2011;Vieira et al, 2013). The application of protease to improve protein digestibility has been studied extensively in poultry (Ghazi, Rooke, & Galbraith, 2003;Ghazi, Rooke, Galbraith, & Bedford, 2002;Marsman et al, 1997;Rubio, Brenes, & Centeno, 2003;Vieira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific enzyme, protease, was suggested adding to the feed efficiency, aimed to improve the protein utilization of the animals and reduce the required amount of dietary protein (and the nitrogen content) (Li et al, 2015;Oxenboll, Pontoppidan, & Fru-Nji, 2011). But it would also be expected to reduce the total content of nitrogen in manure helping to reduce nutrient excretions (Fru-Nji, Kluenter, Morten, & Pontoppidan, 2011;Vieira et al, 2013). The application of protease to improve protein digestibility has been studied extensively in poultry (Ghazi, Rooke, & Galbraith, 2003;Ghazi, Rooke, Galbraith, & Bedford, 2002;Marsman et al, 1997;Rubio, Brenes, & Centeno, 2003;Vieira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…But it would also be expected to reduce the total content of nitrogen in manure helping to reduce nutrient excretions (Fru-Nji, Kluenter, Morten, & Pontoppidan, 2011;Vieira et al, 2013). The application of protease to improve protein digestibility has been studied extensively in poultry (Ghazi, Rooke, & Galbraith, 2003;Ghazi, Rooke, Galbraith, & Bedford, 2002;Marsman et al, 1997;Rubio, Brenes, & Centeno, 2003;Vieira et al, 2013). It has also been reported on rainbow trout (Oncorhynchus mykiss) (Drew et al, 2005) and tilapia (Oreochromis niloticus × O. aureus) (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Zanella et al (1999) (Dosković et al, 2013). Poultry fed proteasecontaining diets had positive effect on CP, lysine and cystine digestibility than those fed the diets without protease (Vieira et al, 2013). In addition, a beneficial effect was found on the ileal digestibility of AAs when the chicks fed acid protease supplementation.…”
Section: Ileal Digestibilitymentioning
confidence: 93%
“…Additionally, there was a main effect of protease on FCR with birds fed diets with protease having a lower FCR than those without(Vieira et al, 2013;walk et al, 2018) Purbojo, LUIS, E. S., Tambunan R. D., and Pamungkas, D. (2004). Additionally, there was a main effect of protease on FCR with birds fed diets with protease having a lower FCR than those without(Vieira et al, 2013;walk et al, 2018) Purbojo, LUIS, E. S., Tambunan R. D., and Pamungkas, D. (2004).…”
mentioning
confidence: 99%
“…Furthermore the significance of interaction of papain crude extract and feed forms for feed conversion ratio (FCR) throughout the observation affirmed the role of crude papain application levels up to 0.07% in diets. Several previous researchers observed the role of supplementation of protease in the diet (Vieira et al, 2013) resulted a better feed intake (Mahejabin et al, 2015), body weight and FCR values to the chicken (Kame et al, 2015).This condition facilitated digestibility of amino acids in the diets to get a better FCR of broilers (Mejia et al, 2011). Similar response was reported by Yadav and Sah (2006)the use of 0.07% and 0.1 % acid protease in diets improved the feed efficiency of layer chicken, while Rada et al(2013)was divergent showed that the exogenous mono-component protease added into low protein broiler diet had no significant effect on both observed growth parameters carcass characteristic.…”
Section: Resultsmentioning
confidence: 99%